Retinal Diseases (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This Special Issue Reprint provides an updated overview of retina and retinal diseases along with therapeutic and diagnostic approaches. The diseases covered include diabetic retinopathy, macular edema, retinoblastoma, age-related macular degeneration, and inherited retinal disorders associated with infantile nystagmus syndrome. Recent advances in therapeutic development approaches, such as gene- and stem-cell-based therapies, are reviewed, and recent advances in the clinical treatment of application, including anti-VEGF and vision rehabilitation and eye exercises, are included. Updates regarding diagnostic and disease-grading methodologies, such as VESsel GENeration (VESGEN) analysis and deep neural networks are also highlighted, offering insights into future directions. In addition, this Reprint describes photoreceptor synapse development and related transcriptome analyses.